Screening method of rice husks for preparing battery negative electrode material, battery negative electrode material and preparation method
By screening and processing rice husks, high-performance lithium-ion battery negative electrode materials are prepared, which solves the problem of poor performance of rice husk materials in the existing technology, improves the stability and cycle life of lithium batteries, and is suitable for commercial production.
Patent Information
- Application Number
- CN202310794506.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing lithium-ion battery anode materials prepared with rice husks have poor cycle stability, first-effect curlon and rate performance, and poor batch stability, which affects the economy, safety and cycle life of lithium batteries.
By heating the rice husks from room temperature to 600-1000°C in air or oxygen atmosphere at a temperature increase rate of 0.5-20°C/min, the weight loss rate at different temperatures was recorded and the thermal gravity curve was drawn, and the cellulose and hemicellulose were calculated. The ratio of carbonization loss to carbonization loss of lignin was screened out, suitable rice husks were pretreated and calcined, and high-performance battery negative electrode materials were prepared.
It improves the first-effect curlost, rate performance and capacity of lithium batteries, ensures stability between batches, extends cycle life, and provides guarantees for the commercial application of negative electrode materials for rice husk preparation.
Smart Images

Figure SMS_1 
Figure HDA0004314557230000011 
Figure HDA0004314557230000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery materials, and relates to a method for screening rice husks for preparing battery negative electrode materials, a battery negative electrode material and a preparation method. Background Art
[0002] With the rapid development of science and technology, various electronic devices and electric vehicles have been widely used, and the requirements for chemical power sources are getting higher and higher. As a kind of chemical power source, lithium-ion batteries have the advantages of high battery voltage, large specific capacity, high energy density, great development potential, low self-discharge rate, and no memory effect. They have been widely used in electronic devices. At present, the majority of negative electrode materials of commercial lithium-ion batteries are graphite negative electrodes. Graphite negative electrodes are divided into artificial graphite and natural graphite. They have their own advantages and disadvantages as negative electrode materials. Artificial graphite has the advantage of stable cycle, but its capacity is generally lower than natural graphite. Although natural graphite has the advantage of high capacity, its fatal weakness is that its capacity decays quickly during the cycle.
[0003] China is a large agricultural country, and its rice production ranks first in the world. Rice husk is the largest byproduct of rice processing, accounting for 20% of rice by weight. In China, most rice husks are directly burned, which seriously pollutes the environment. Rice husks are composed of organic and inorganic substances, among which organic substances are mainly cellulose, lignin, and hemicellulose, which can be used as a carbon source for negative electrode materials of lithium-ion batteries. Using rice husks as raw materials to prepare carbon materials not only avoids the negative impact of rice husk incineration and landfill on the environment, but also obtains cheap carbon materials through modification and calcination. Using this high-performance and cheap carbon material as a negative electrode material and applying it to lithium-ion batteries can effectively alleviate the problem of energy shortage.
[0004] For example, Chinese patent document CN103647043A discloses a method for preparing negative electrode materials for lithium-ion secondary batteries, using rice husk as raw material, carbonizing at 200-700°C, and high-temperature treatment at 700-1000°C in an atmosphere of hydrogen or hydrogen and argon to prepare electrode materials. Chinese patent document CN106848249A discloses a method for preparing negative electrode materials for lithium-ion batteries using SiO2@C core-shell composites, carbonizing rice husks, pickling, and ball milling to prepare negative electrode materials. Chinese patent document CN110429264A discloses a method for preparing rice husk-based negative electrode materials using rice husk as raw material, acid hydrolysis treatment, ZnCl2 activation, and asphalt treatment. Chinese patent document CN112397701A discloses a rice husk-based silicon oxide / carbon composite negative electrode material and its preparation method and application, using rice husk, acid solution, zinc chloride, carbon source, reducing agent, ethanol, and deionized water as raw materials to prepare composite materials. Chinese patent document CN113178564A discloses a silicon dioxide-carbon composite material and its preparation method and application. Rice husk is used as raw material, and a stable silicon-carbon ratio is obtained by controlling the concentration of citric acid solution, solution temperature, stirring speed and time.
[0005] The document "Study on the Preparation of Lithium-ion Battery Negative Electrode Materials from Rice Husk" discussed the effects of heating rate and different concentrations of NaOH solution on the performance of rice husk carbon materials, and screened out the best experimental conditions: heating rate of 5℃ / min, pyrolysis temperature of 700℃, and alkali concentration of 2.0mol / L. Under the best experimental conditions, the reversible capacity of the obtained carbon material after 10 charge and discharge cycles was about 206.1mA·h / g.
[0006] The document "Preparation of Lithium-ion Battery Carbon Anode Material from Rice Husk" discussed the effects of carbonization temperature, heating rate, and NaOH solution concentration on the performance of rice husk carbon materials, and screened out the best experimental conditions: when the pyrolysis temperature is lower than 250℃ and higher than 530℃, the heating rate is 10℃ / min, and the heating rate is 5℃ / min in the range of 250-530℃; boil rice husk with 3mol / L HCl for 1h, and boil 2mol / LNaOH solution for 2h. Under these conditions, the first charge capacity of the obtained rice husk carbon material is 678mA·h / g, the first discharge capacity is 239mA·h / g, and the reversible capacity of 10 charge and discharge cycles is about 206mA·h / g.
[0007] Although certain achievements have been made in the preparation of carbon materials using rice husks, the existing carbon materials prepared from rice husks, when used as negative electrode materials for lithium batteries, have problems such as poor comprehensive performance of the resulting lithium-ion batteries, such as cycle stability, first-effect coulomb and rate performance, and poor batch stability, which directly affects the economy, safety and cycle life of lithium batteries. Summary of the invention
[0008] The purpose of the present invention is to provide a method for screening rice husks for preparing battery negative electrode materials. The negative electrode material prepared from the rice husks screened by the method has the advantages of high first-effect coulomb, high rate performance and capacity, and good stability between batches, which can significantly improve the stability and cycle life of the lithium battery.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] A method for screening rice husks for preparing negative electrode materials for batteries, wherein the rice husks are heated from room temperature to 600-1000°C at a heating rate of 0.5-20°C / min in an air or oxygen atmosphere, and the weight loss rate of the rice husks at different temperatures is recorded, and a thermogravimetric curve is plotted;
[0011] The ratio of the weight of carbonization loss of cellulose and hemicellulose in the rice husk to the weight of carbonization loss of lignin in the rice husk is calculated according to the thermogravimetric curve, and the rice husk used for preparing the negative electrode material of the battery is screened.
[0012] Wherein, weight loss rate = (mass of rice husk before roasting - mass of rice husk at a certain temperature during roasting) / (mass of rice husk before roasting) × 100%.
[0013] Optionally, in the method for selecting rice husks for preparing negative electrode materials for batteries provided by the present invention, the rice husks are heated from room temperature to 50°C for a certain period of time, such as 20-40 minutes, in order to remove moisture from the rice husks. This step can also be omitted, and the rice husks are directly heated from room temperature to 600-1000°C, which does not affect the selection of the rice husks.
[0014] Optionally, in the method for screening rice husks for preparing battery negative electrode materials provided by the present invention, the heating rate is 0.5-10° C. / min.
[0015] Optionally, in the method for screening rice husks for preparing negative electrode materials for batteries provided by the present invention, the carbonization temperature of the cellulose and hemicellulose is 250-350° C., and the carbonization temperature of the lignin is 350-500° C. Specifically, the ratio of the difference in weight loss rate in the range of 250-350° C. to the difference in weight loss rate in the range of 350-500° C. in the thermogravimetric curve is the ratio of the weight loss of cellulose and hemicellulose in the rice husk due to carbonization to the weight loss of lignin due to carbonization.
[0016] Optionally, in the method for screening rice husks for preparing battery negative electrode materials provided by the present invention, the ratio of the weight of the carbonization loss of cellulose and hemicellulose to the weight of the carbonization loss of lignin is recorded as N, and rice husks with N>1.14 are selected to prepare battery negative electrode materials. Lithium batteries made from battery negative electrode materials prepared from rice husks with N>1.14 have high first coulomb efficiency, high capacity, stable cycle performance and long life, and lithium batteries made from battery negative electrode materials prepared from each batch have stable comprehensive performance, which provides a guarantee for the commercial application of negative electrode materials prepared from rice husks.
[0017] In the screening method of rice husks for preparing battery negative electrode materials provided by the present invention, the origin of the rice husks is not limited, and rice husks from any origin are applicable to the screening method provided by the present invention. For example, rice husks from Heilongjiang, Hunan, Hubei, Sichuan, Liaoning and other places are applicable.
[0018] The present invention also provides a method for preparing a negative electrode material for a battery, comprising the following steps:
[0019] Screening: Screening rice husks according to the above-mentioned method for screening rice husks for preparing battery negative electrode materials;
[0020] Pretreatment: washing the screened rice husks with alkaline solution or acidic solution and deionized water in sequence to obtain pretreated rice husks;
[0021] Calcination: Calcinate and crush the pretreated rice husk in an inert atmosphere to obtain a negative electrode material for a battery.
[0022] Optionally, in the method for preparing the battery negative electrode material provided by the present invention, the alkaline solution is a sodium hydroxide solution; preferably, the concentration of the sodium hydroxide solution is 1-5M, more preferably 2.5-5M. Washing with an alkaline solution can remove silicon dioxide and impurities (such as phosphorus, potassium, magnesium, calcium, sodium, iron, etc.) in the rice husk. Washing with an alkaline solution will not introduce a new carbon source, and the silicon dioxide in the rice husk is removed. The battery negative electrode material finally obtained is a pure carbon material. The performance of the pure carbon material obtained from the rice husk as a battery negative electrode material can be examined separately, providing guidance for the further application of the rice husk.
[0023] Optionally, in the method for preparing the battery negative electrode material provided by the present invention, the washing method of the alkaline solution is immersion, the immersion time is 20-120 min, preferably 60-120 min; the immersion temperature is 80°C-120°C, preferably 95-120°C.
[0024] Optionally, in the preparation method of the battery negative electrode material provided by the present invention, the acidic solution is selected from at least one of hydrochloric acid, citric acid, sulfuric acid, nitric acid, acetic acid and oxalic acid solutions; preferably, the concentration of the acidic solution is 1-5M, more preferably 1-3M. The impurities (such as phosphorus, potassium, magnesium, calcium, sodium, iron, etc.) in the rice husk can be removed by washing with an acidic solution, but the silicon dioxide will not be removed. The final battery negative electrode material is a carbon material containing silicon dioxide. When inorganic strong acids such as hydrochloric acid, sulfuric acid and nitric acid are used, no new carbon source is introduced. The rice husk is both a carbon source and a silicon source. The performance of the carbon material containing silicon dioxide prepared from the rice husk as a battery negative electrode material can be examined to provide basic guidance for subsequent applications.
[0025] Optionally, in the method for preparing the negative electrode material of the battery provided by the present invention, the washing method of the acidic solution is soaking, and the soaking time is 20-120 minutes, preferably 60-120 minutes; the soaking temperature is 20°C-120°C, preferably 70-90°C. Optionally, in the method for preparing the negative electrode material of the battery provided by the present invention, the pretreated rice husk can be mixed with other carbon materials such as graphite, asphalt, graphene, conductive carbon black, reduced graphene oxide, etc. before calcination according to actual needs, and then roasted to obtain a composite carbon material, which can further improve the conductivity of the obtained carbon material and simultaneously inhibit the volume expansion of silicon particles, thereby improving the cycle performance of the battery.
[0026] Optionally, in the preparation method of the battery negative electrode material provided by the present invention, the calcination parameters are not specifically limited, and conventional parameters in the industry can be used for carbonization. The present invention recommends a calcination temperature of 600-1000°C, a time of 2-6h, and a heating rate of 0.5-20°C / min, preferably 0.5-10°C / min, and more preferably 0.5-5°C / min.
[0027] Optionally, in the preparation method of the battery negative electrode material provided by the present invention, the pulverizing method is not specifically limited, and a suitable pulverizing method can be selected according to the actual strength required, such as any one selected from mortar, ball mill, air flow mill and mechanical impact mill.
[0028] Optionally, in the method for preparing the battery negative electrode material provided by the present invention, the inert gas is nitrogen or argon.
[0029] The present invention also provides a battery negative electrode material, which is prepared by the above-mentioned method for preparing the battery negative electrode material.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] 1. In view of the negative electrode materials made from rice husks, a byproduct of rice, in the prior art, the lithium-ion batteries finally obtained have problems such as low first-effect coulomb, poor rate performance, and poor stability and cycle performance. Most of the prior art methods for preparing negative electrode materials from rice husks are improved, such as adjusting the calcination method (pre-calcination combined with controlling the calcination temperature and heating rate, etc.), improving the pretreatment method (using acid washing, alkali washing), etc., but the effect is not ideal. In this way, although rice husks are used as waste and the production cost of batteries is reduced, due to the poor overall performance and large performance differences between batches, commercial-scale production is impossible.
[0032] In view of the above problems, the present invention provides a method for screening rice husks for preparing battery negative electrode materials. In an air atmosphere, the rice husks are heated from room temperature to 600-1000°C at a heating rate of 0.5-20°C / min, and the weight loss rate of the rice husks at different temperatures is recorded, and a thermogravimetric curve is drawn; and the ratio of the weight lost by carbonization of cellulose and hemicellulose in the rice husk to the weight lost by carbonization of lignin is calculated according to the thermogravimetric curve. The battery negative electrode material prepared from the rice husks screened by the ratio has excellent comprehensive performance, especially the cycle stability, first effective coulomb and rate performance. The performance of the negative electrode materials prepared in each batch is stable, which provides a guarantee for the safety and cycle life of the lithium battery, and also provides a guarantee for the commercial large-scale production of negative electrode materials prepared from rice husks.
[0033] 2. The preparation method of the battery negative electrode material provided by the present invention can screen rice husks according to the ratio of the carbonization loss weight of cellulose and hemicellulose to the carbonization loss weight of lignin according to the actual performance or research and development requirements of the negative electrode material, and then wash the screened rice husks with alkali or acid, wash with water, and then calcine and crush under an inert atmosphere to obtain the negative electrode material. When the negative electrode material is prepared from rice husks with a ratio of the carbonization loss weight of cellulose and hemicellulose to the carbonization loss weight of lignin greater than 1.14, the added value of the rice husks is greatly improved, the carbon source in the rice husks is fully utilized, the waste of resources is avoided, and carbon emissions are reduced, which provides a basic guarantee for the wide application of rice husks in the preparation of negative electrode materials.
[0034] 3. The preparation method of the battery negative electrode material provided by the present invention directly uses rice husk, a byproduct of rice, as raw material, and realizes the reuse of crop byproducts, which is not only beneficial to environmental protection, but also saves production costs, meets the requirements of the country to vigorously develop the reuse of natural waste crops, and improves the economic, social and ecological benefits of rice. In addition, the preparation method is simple to operate, low-cost and environmentally friendly.
[0035] 4. The preparation method of the battery negative electrode material provided by the present invention uses a bio-based carbon material made from rice husks, which is stable and easy to store and has a porous structure. The organic matter therein can provide good skeleton support after carbonization, so that the material has a good three-dimensional spatial structure. The integrity of this structure is conducive to charge diffusion and rapid ion transport, thereby improving its electrochemical performance when used as a negative electrode material. When used for the negative electrode of a lithium-ion battery, it has the advantages of high first efficiency, high capacity, stable cycle performance and long life, and excellent electrochemical comprehensive performance, and is expected to be applied to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Thermogravimetric curve of rice husk used in Example 1 of the present invention;
[0037] Figure 2 Thermogravimetric curve of rice husk used in Example 2 of the present invention;
[0038] Figure 3 Thermogravimetric curve of rice husk used in Example 3 of the present invention;
[0039] Figure 4 This is the thermogravimetric curve of rice husk used in Comparative Example 1 of the present invention;
[0040] Figure 5 This is a cycle performance diagram of CR2032 button batteries made from the negative electrode materials prepared in Examples 1-3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0041] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.
[0042] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.
[0043] Example 1
[0044] This embodiment provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0045] Screening: In an air atmosphere, place 10 mg of rice husk produced in Liaoning (denoted as PJ-DK) in a crucible, keep the bottom flat and in full contact with the crucible, heat the crucible containing rice husk from room temperature to 50°C at a rate of 10°C / min and keep it for 30 minutes (the purpose is to remove moisture in the rice husk), then heat the crucible containing rice husk to 800°C at a rate of 10°C / min, record the weight change of the rice husk, and draw a curve with the mass change rate as the ordinate and the temperature as the abscissa, such as Figure 1 As shown, the mass change rate of the second curve (in the range of 250-350°C) is the percentage of the carbonization loss weight of cellulose and hemicellulose in the total mass of rice husk (43.43%), and the mass change rate of the third curve (in the range of 350-500°C) is the percentage of the carbonization loss weight of lignin in the total mass of rice husk (30.83%). The ratio of the carbonization loss weight of cellulose and hemicellulose to the carbonization loss weight of lignin is calculated to be about 1.41; Figure 1 9.13% of the weight is free water and bound water volatilized from the rice husk, and 9.34% is the weight lost due to changes in the carbon layer structure caused by high temperature.
[0046] Pretreatment: 2 g of rice husk produced in Liaoning was placed in 20 mL of 3.0 M sodium hydroxide solution, soaked at 100 ° C for 2 h, washed with deionized water for 3 times, and finally dried at 80 ° C for 12 h to obtain the pretreated rice husk;
[0047] Calcination: The pretreated rice husk is heated from 50°C to 900°C at a rate of 5°C / min and maintained at this temperature for 2.0h. After naturally cooling to room temperature, the obtained product is crushed to 200 mesh by ball milling to obtain the battery negative electrode material.
[0048] Example 2
[0049] This embodiment provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0050] Screening: In an air atmosphere, place 10 mg of rice husk produced in Hunan (referred to as HN-DK) in a crucible, keep the bottom flat and in full contact with the crucible, heat the crucible containing rice husk from room temperature to 50°C at a rate of 10°C / min and keep it for 30 minutes, then heat the crucible containing rice husk to 800°C at a rate of 10°C / min, record the weight change of rice husk, and draw a curve with the mass change rate as the ordinate and the temperature as the abscissa, such as Figure 2As shown, the mass change rate of the second curve (in the range of 250-350°C) is the percentage of the carbonization loss weight of cellulose and hemicellulose to the total mass of rice husk (42.10%), and the mass change rate of the third curve (in the range of 350-500°C) is the percentage of the carbonization loss weight of lignin to the total mass of rice husk (33.81%). The ratio of the carbonization loss weight of cellulose and hemicellulose to the carbonization loss weight of lignin is calculated to be about 1.25. Figure 2 7.22% is the free water and bound water volatilized from the rice husk, and 4.69% is the weight lost due to the change of carbon layer structure caused by high temperature.
[0051] Pretreatment: 2 g of rice husk produced in Hunan was placed in 20 mL of 3.0 M sodium hydroxide solution, soaked at 100 ° C for 2 h, washed with deionized water for 3 times, and finally dried at 80 ° C for 12 h to obtain the pretreated rice husk;
[0052] Calcination: The pretreated rice husk is heated from 50°C to 900°C at a rate of 5°C / min and maintained at this temperature for 2.0h. After naturally cooling to room temperature, the obtained product is crushed to 200 mesh by ball milling to obtain the battery negative electrode material.
[0053] Example 3
[0054] This embodiment provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0055] Screening: In an air atmosphere, 10 mg of rice husk produced in Heilongjiang (recorded as HLJ-DK) was placed in a crucible, keeping the bottom flat and in full contact with the crucible. The crucible containing the rice husk was heated from room temperature to 50°C at a rate of 10°C / min and kept for 30 minutes. Then, the crucible containing the rice husk was heated to 800°C at a rate of 10°C / min. The weight change of the rice husk was recorded, and a curve was drawn with the mass change rate as the ordinate and the temperature as the abscissa, such as Figure 3 As shown, the mass change rate of the second curve (in the range of 250-350°C) is the percentage of the carbonization loss weight of cellulose and hemicellulose to the total mass of rice husk (43.17%), and the mass change rate of the third curve (in the range of 350-500°C) is the percentage of the carbonization loss weight of lignin to the total mass of rice husk (37.64%). The ratio of the carbonization loss weight of cellulose and hemicellulose to the carbonization loss weight of lignin is calculated to be about 1.15. Figure 3 3.39% is the free water and bound water volatilized from the rice husk, and 1.69% is the weight lost due to the change of carbon layer structure caused by high temperature.
[0056] Pretreatment: 2 g of rice husk produced in Heilongjiang was placed in 20 mL of 3.0 M sodium hydroxide solution, soaked at 100 ° C for 2 h, washed with deionized water for 3 times, and finally dried at 80 ° C for 12 h to obtain the pretreated rice husk;
[0057] Calcination: The pretreated rice husk is heated from 50°C to 900°C at a rate of 5°C / min and maintained at this temperature for 2.0h. After naturally cooling to room temperature, the obtained product is crushed to 200 mesh by ball milling to obtain the battery negative electrode material.
[0058] Example 4
[0059] This embodiment provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0060] Screening: In an air atmosphere, 10 mg of rice husk produced in Liaoning (denoted as PJ-DK) was placed in a crucible, keeping the bottom flat and in full contact with the crucible, and the crucible containing the rice husk was heated from room temperature to 50°C at a rate of 5°C / min and kept for 30 minutes (the purpose was to remove moisture in the rice husk), and then the crucible containing the rice husk was heated to 600°C at a rate of 5°C / min, and the weight change of the rice husk was recorded, and a curve with the mass change rate as the ordinate and the temperature as the abscissa was drawn, wherein the mass change rate of the second curve (within the range of 250-350°C) was the percentage of the carbonization loss weight of cellulose and hemicellulose in the total mass of the rice husk, and the mass change rate of the third curve (within the range of 350-500°C) was the percentage of the carbonization loss weight of lignin in the total mass of the rice husk, and the ratio of the carbonization weight loss of cellulose and hemicellulose to the carbonization weight loss of lignin was calculated, which was about 1.51;
[0061] Pretreatment: 2 g of rice husk produced in Liaoning was placed in 20 mL of 2.0 M hydrochloric acid solution, soaked at 100 ° C for 2 h, washed with deionized water for 3 times, and finally dried at 80 ° C for 12 h to obtain the pretreated rice husk;
[0062] Calcination: The pretreated rice husk is heated from 50°C to 700°C at a rate of 15°C / min and maintained at this temperature for 6.0 hours. After naturally cooling to room temperature, the obtained product is ball-milled to 200 mesh to obtain the battery negative electrode material.
[0063] Example 5
[0064] This embodiment provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0065] Screening: In an air atmosphere, 10 mg of rice husk produced in Liaoning (denoted as PJ-DK) was placed in a crucible, keeping the bottom flat and in full contact with the crucible, and the crucible containing the rice husk was heated from room temperature to 50°C at a rate of 1°C / min and kept for 30 minutes (the purpose was to remove moisture in the rice husk), and then the crucible containing the rice husk was heated to 700°C at a rate of 1°C / min, and the weight change of the rice husk was recorded, and a curve with the mass change rate as the ordinate and the temperature as the abscissa was drawn, wherein the mass change rate of the second curve (within the range of 250-350°C) was the percentage of the carbonization loss weight of cellulose and hemicellulose in the total mass of the rice husk, and the mass change rate of the third curve (within the range of 350-500°C) was the percentage of the carbonization loss weight of lignin in the total mass of the rice husk, and the ratio of the carbonization weight loss of cellulose and hemicellulose to the carbonization weight loss of lignin was calculated, which was about 1.53;
[0066] Pretreatment: 2 g of rice husk produced in Liaoning was placed in 20 mL of 1.0 M sodium hydroxide solution, soaked at 120 ° C for 1 h, washed with deionized water 3 times, and finally dried at 80 ° C for 12 h to obtain the pretreated rice husk;
[0067] Calcination: The pretreated rice husk is heated from 50°C to 600°C at a rate of 10°C / min and maintained at this temperature for 4.0 hours. After naturally cooling to room temperature, the obtained product is crushed to 200 mesh by ball milling to obtain the battery negative electrode material.
[0068] Example 6
[0069] This embodiment provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0070] Screening: In an air atmosphere, 10 mg of rice husk produced in Liaoning (denoted as PJ-DK) was placed in a crucible, keeping the bottom flat and in full contact with the crucible, and the crucible containing the rice husk was heated from room temperature to 50°C at a rate of 15°C / min and kept for 30 minutes (the purpose was to remove moisture in the rice husk), and then the crucible containing the rice husk was heated to 900°C at a rate of 15°C / min, and the weight change of the rice husk was recorded, and a curve with the mass change rate as the ordinate and the temperature as the abscissa was drawn, wherein the mass change rate of the second curve (within the range of 250-350°C) was the percentage of the carbonization loss weight of cellulose and hemicellulose in the total mass of the rice husk, and the mass change rate of the third curve (within the range of 350-500°C) was the percentage of the carbonization loss weight of lignin in the total mass of the rice husk, and the ratio of the carbonization loss weight of cellulose and hemicellulose to the carbonization loss weight of lignin was calculated, which was about 1.40;
[0071] Pretreatment: 2 g of rice husk produced in Liaoning was placed in 20 mL of 5.0 M sodium hydroxide solution, soaked at 80 ° C for 30 min, washed with deionized water for 3 times, and finally dried at 80 ° C for 12 h to obtain the pretreated rice husk;
[0072] Calcination: The pretreated rice husk is heated from 50°C to 800°C at a rate of 20°C / min and maintained at this temperature for 5.0 hours. After naturally cooling to room temperature, the obtained product is crushed to 200 mesh by ball milling to obtain the battery negative electrode material.
[0073] Example 7
[0074] This embodiment provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0075] Screening: In an air atmosphere, 10 mg of rice husk produced in Liaoning (denoted as PJ-DK) was placed in a crucible, keeping the bottom flat and in full contact with the crucible, and the crucible containing the rice husk was heated from room temperature to 50°C at a rate of 20°C / min and kept for 30 minutes (the purpose was to remove moisture in the rice husk), and then the crucible containing the rice husk was heated to 1000°C at a rate of 20°C / min, and the weight change of the rice husk was recorded, and a curve with the mass change rate as the ordinate and the temperature as the abscissa was drawn, wherein the mass change rate of the second curve (within the range of 250-350°C) was the percentage of the carbonization loss weight of cellulose and hemicellulose in the total mass of the rice husk, and the mass change rate of the third curve (within the range of 350-500°C) was the percentage of the carbonization loss weight of lignin in the total mass of the rice husk, and the ratio of the carbonization loss weight of cellulose and hemicellulose to the carbonization loss weight of lignin was calculated, which was about 1.35;
[0076] Pretreatment: 2 g of rice husk produced in Liaoning was placed in 20 mL of 4.0 M nitric acid solution, soaked at 40 ° C for 50 min, washed with deionized water for 3 times, and finally dried at 80 ° C for 12 h to obtain the pretreated rice husk;
[0077] Calcination: The pretreated rice husk is heated from 50°C to 1000°C at a rate of 1°C / min and maintained at this temperature for 3.0 hours. After naturally cooling to room temperature, the obtained product is ball-milled to 200 mesh to obtain the battery negative electrode material.
[0078] Example 8
[0079] This embodiment provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0080] Screening: In an air atmosphere, 10 mg of rice husk produced in Hubei (referred to as HB-DK) was placed in a crucible, keeping the bottom flat and in full contact with the crucible. The crucible containing the rice husk was heated from room temperature to 50°C at a rate of 10°C / min and kept for 30 minutes (the purpose was to remove moisture from the rice husk). The crucible containing the rice husk was then heated to 800°C at a rate of 10°C / min. The weight change of the rice husk was recorded, and a curve with the mass change rate as the ordinate and the temperature as the abscissa was drawn. The mass change rate of the second curve (within the range of 250-350°C) was the percentage of the carbonization loss weight of cellulose and hemicellulose in the total mass of the rice husk, and the mass change rate of the third curve (within the range of 350-500°C) was the percentage of the carbonization loss weight of lignin in the total mass of the rice husk. The ratio of the carbonization loss weight of cellulose and hemicellulose to the carbonization loss weight of lignin was calculated, which was about 1.40.
[0081] Pretreatment: 2 g of rice husk produced in Hubei was placed in 20 mL of 3.0 M sodium hydroxide solution, soaked at 100 ° C for 2 h, washed with deionized water for 3 times, and finally dried at 80 ° C for 12 h to obtain the pretreated rice husk;
[0082] Calcination: The pretreated rice husk is heated from 50°C to 900°C at a rate of 5°C / min and maintained at this temperature for 2.0h. After naturally cooling to room temperature, the obtained product is crushed to 200 mesh by ball milling to obtain the battery negative electrode material.
[0083] Comparative Example 1
[0084] This comparative example provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0085] Screening: In an air atmosphere, 10 mg of rice husk produced in Chongqing (referred to as CQ-DK) was placed in a crucible, keeping the bottom flat and in full contact with the crucible. The crucible containing the rice husk was heated from room temperature to 50°C and kept for 30 min. The crucible containing the rice husk was then heated to 800°C at a rate of 10°C / min. The weight change of the rice husk was recorded, and a curve was drawn with the mass change rate as the ordinate and the temperature as the abscissa, such as Figure 4 As shown, the mass change rate of the second curve (in the range of 250-350°C) is the percentage of the carbonization loss weight of cellulose and hemicellulose in the total mass of rice husk (41.10%), and the mass change rate of the third curve (in the range of 350-500°C) is the percentage of the carbonization loss weight of lignin in the total mass of rice husk (37.91%). The ratio of the carbonization loss weight of cellulose and hemicellulose to the carbonization loss weight of lignin is calculated to be about 1.11; Figure 4 4.19% is the free water and bound water volatilized from the rice husk, and 1.19% is the weight lost due to the change in the carbon layer structure caused by high temperature.
[0086] Pretreatment: 2 g of rice husk produced in Chongqing was placed in 20 mL of 3.0 M sodium hydroxide solution, soaked at 100 ° C for 2 h, washed with deionized water for 3 times, and finally dried at 80 ° C for 12 h to obtain the pretreated rice husk;
[0087] Calcination: The pretreated rice husk is heated from 50°C to 900°C at a rate of 5°C / min and maintained at this temperature for 2.0h. After naturally cooling to room temperature, the obtained product is crushed to 200 mesh by ball milling to obtain the battery negative electrode material.
[0088] Experimental example
[0089] The battery negative electrode materials prepared in each embodiment and comparative example were placed in an agate jar and ground for 1 hour, 400 mg of the ground material was weighed and mixed with a conductive agent acetylene black, a binder CMC (carboxymethyl cellulose) and a binder SBR in a mass ratio of 8:1:0.5:0.5, stirred for 5 hours to make a slurry, coated on a copper foil, and vacuum dried for 12 hours, and then pressed to obtain a lithium ion battery negative electrode sheet; then in a glove box filled with argon, the prepared lithium ion battery negative electrode sheet was assembled with a positive electrode sheet (lithium sheet) to obtain a CR2032 button battery, the electrolyte used LiPF6 as a solute, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1 as a solvent, and the diaphragm was Celgard 2400. The assembled CR2032 button-type battery was tested, and the battery system was used to test the first cycle charge and discharge performance of the battery under constant current, with the charge and discharge voltage range of 0.01-2V. The test results are shown in the following table.
[0090] Table 1
[0091]
[0092] Combining the data in the above table Figure 5 It can be seen that the material made from rice husks in which the ratio of the weight loss of cellulose and hemicellulose carbonization to the weight loss of lignin carbonization in Examples 1 to 7 is greater than 1.14 is used as the negative electrode material, and the capacity retention rate is better after 100 cycles; the negative electrode material made from rice husks in which the ratio of the weight loss of cellulose and hemicellulose carbonization to the weight loss of lignin carbonization is less than 1.14 in Comparative Example 1, the capacity retention rate does not reach 80% after 100 cycles.
[0093] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A method for screening rice husks for preparing negative electrode materials for batteries, characterized in that: The steps include: In an air or oxygen atmosphere, the rice husk is heated from room temperature to 600-1000°C at a heating rate of 0.5-20°C / min, and the weight loss rate of the rice husk at different temperatures is recorded, and a thermogravimetric curve is drawn; The ratio of the weight of carbonization loss of cellulose and hemicellulose in the rice husk to the weight of carbonization loss of lignin in the rice husk is calculated according to the thermogravimetric curve, and the rice husk used for preparing the negative electrode material of the battery is screened.
2. The screening method according to claim 1, characterized in that The heating rate is 0.5-10°C / min.
3. The screening method according to claim 1, characterized in that The carbonization temperature of the cellulose and hemicellulose is 250-350°C, and the carbonization temperature of the lignin is 350-500°C.
4. The screening method according to claim 1, wherein The ratio of the weight loss of the cellulose and hemicellulose due to carbonization to the weight loss of the lignin due to carbonization is recorded as N, and rice husks with N>1.14 are selected to prepare the negative electrode material for the battery.
5. A method for preparing a negative electrode material for a battery, characterized in that: The steps include: Screening: Screening rice husks according to the method for screening rice husks for preparing battery negative electrode materials according to any one of claims 1 to 4; Pretreatment: washing the screened rice husks with alkaline solution or acidic solution and deionized water in sequence to obtain pretreated rice husks; Calcination: Calcinate and crush the pretreated rice husk in an inert atmosphere to obtain a negative electrode material for a battery.
6. The preparation method according to claim 5, characterized in that: The alkaline solution is a sodium hydroxide solution; preferably, the concentration of the sodium hydroxide solution is 1-5M, more preferably 2.5-5M; and / or The acidic solution is selected from at least one of hydrochloric acid, citric acid, sulfuric acid, nitric acid, acetic acid and oxalic acid solutions; preferably, the concentration of the acidic solution is 1-5M, more preferably 1-3M.
7. The preparation method according to claim 5, characterized in that: The alkaline solution is washed by soaking for 20-120 minutes, preferably 60-120 minutes; the soaking temperature is 80°C-120°C, preferably 95-120°C; and / or The acid solution is washed by soaking for 20-120 minutes, preferably 60-120 minutes; the soaking temperature is 20°C-120°C, preferably 70-90°C.
8. The preparation method according to claim 5, characterized in that: The calcination temperature is 600-1000°C, the time is 2-6h, and the heating rate is 0.5-20°C / min, preferably 0.5-10°C / min, and more preferably 0.5-5°C / min.
9. The preparation method according to claim 5, characterized in that: The pulverizing method is selected from any one of mortar, ball mill, air flow pulverizing and mechanical impact mill, preferably ball mill.
10. A battery negative electrode material, characterized in that: The negative electrode material is prepared by the method for preparing the negative electrode material for a battery according to any one of claims 5 to 9.
